A notational analysis of elite tennis strategy - O'Donoghue, P.; Ingram, B. (Journal of Sports Sciences, 2001)
A notational analysis of singles events at all four Grand Slam tournaments between 1997 and 1999 was conducted to determine the influence of the sex of the player and court surface on elite tennis strategy. Rallies of 7.1 +/- 2.0 s in women's singles were significantly longer than those in men's singles (5.2 +/- 1.8 s; P < 0.001). Rallies of 6.3 +/- 1.8 s at the Australian Open, 7.7 +/- 1.7 s at the French Open, 4.3 +/- 1.6 s at Wimbledon and 5.8 +/- 1.9 s at the US Open were recorded. Rallies were significantly longer at the French Open than at any other tournament (P< 0.05) and significantly shorter at Wimbledon than at any other tournament (P< 0.05). In women's singles, 52.8 +/- 12.4% of points were baseline rallies, significantly more than in men's singles (28.6 +/- 19%; P < 0.001). The proportion of baseline rallies played at the French Open (51.9 +/- 14.2% of points) was significantly greater than at the Australian Open (46.6 +/- 12.5%), Wimbledon (19.7 +/- 19.4%) and the US Open (35.4 +/- 19.5%; P < 0.05). The results show that both the sex of the player and surface of the court have a significant influence on the nature of singles tennis at Grand Slam tournaments.